A unique rail project – SørVestBanen - Langeland, Anders (Proceedings from the Annual Transport Conference at Aalborg University, 2007)
The gap between transport work done and the goals of shifting from road transport to more environmentally sustainable modes keep widening (EEA 2006). Rail transport inter-cities could be an instrument for such a shift, however the rail infrastructure has suffered a lack of investment for 30 years. SørVestBanen is a vision and project that could facilitate such a shift through basically upgrading the existing track and offer high frequency services, both for passengers and freight.